Natural causes [compact disc, unabridged] : an epidemic of wellness, the certainty of dying, and killing ourselves to live longer - Ehrenreich, Barbara (Hachette Audio, 2018)
Barbara Ehrenreich describes how people over prepare and worry way too much about what is inevitable. One by one, she topples the shibboleths that guide people's attempts to live a long, healthy life, from the importance of preventive medical screenings to the concepts of wellness and mindfulness, from dietary fads to fitness culture.